Salivary biomarkers (Vitamin D, Calcium, and Estrogen Hormone) in postmenopausal women with osteoporosis - Ameera Y AL-Amiry; Areej A Najem (Wolters Kluwer Medknow Publications, 2023)
Background: Osteoporosis is a systemic skeletal disease that weakens bones by lowering mineral density and causing micro-architectural degradation of bony tissue. Aim: This study was conducted to examine the use of vitamin D, calcium, and estrogen levels in saliva as biomarkers for early detection of osteoporosis. Materials and Methods: Ninety postmenopausal women were divided into three groups based on T-scores from dual-energy X-ray absorptiometry scans. The groups consist of 30 women with osteoporosis, 30 women with osteopenia, and 30 women serving as controls. The enzyme-linked immunosorbent assay was used to look for vitamin D and estrogen in the saliva by specific vitamin D3 and estradiol kits. Calcium concentrations were measured by a colorimetric method. Results: The level of salivary biomarkers (vitamin D, calcium, and estrogen) showed a clear distinction between the groups analyzed. Salivary estrogen and vitamin D levels were significantly lower in patients with osteoporosis compared to those with osteopenia and controls. The highest concentration of calcium was found in the osteoporosis group's saliva compared to the other groups. Conclusion: The results highlight the significance of vitamin D, calcium, and estrogen in saliva as a simple, noninvasive biomarker in diagnosing postmenopausal osteoporosis.